Analysis of Water Availability and Demand in The Kromong II Dam Irrigation Mojokerto Regency - Kameswara, Nanda Galuh; Nusantara, Danayanti Azmi Dewi (Politeknik Negeri Lhokseumawe, 2024)
East Java Province has authority over the irrigation area of Mojokerto Regency, one of which is the Irrigation Area of Kromong II which has an area of 1,055 Ha. Kromong Dam is located in the Kromong River, Sajen Village, Mojokerto Regency. The main problem in the Kromong II Irrigation Area is the lack of irrigation water available with the water needs of the rice fields during the dry season, and this was caused by changes in farmers' cropping patterns that exceed planning. Because of this, it is necessary to optimize profits with the land area that best suits the type of plant and water availability. Calculation of water availability uses the F.J Mock method by including rainfall and potential evapotranspiration data. This calculation is followed by an analysis of plant water needs which are adjusted to the planned planting pattern. The analysis in this research used a linear program assisted by QM for Windows 5. From the optimization results after adding water from four pump wells with a capacity of 20 lt/sec, a planting intensity of 200% was obtained in the paddy-paddy-crop planting pattern, with profits obtained greater than the existing amount of Rp 43.176.461.200,-.Keywords: Irrigation Area; Irrigartion; Planting Patterns; Linear Program; Optimization.